Public procurement for innovation in developing countries: The case of Petrobras - Ribeiro, Cássio Garcia [UNESP]; Furtado, André Tosi (Edward Elgar Publishing, 2015)
The public sector is a major user of many goods and services that support the functioning of the machinery of state and help meet the basic needs of the population. Government procurement plays a leading role in the promotion of domestic industry, especially given the magnitude of this market. Some research shows that government procurement accounts for 10-16 per cent of gross domestic product (GDP) in developed countries (Hoekman and Mavroidis, 1995; Audet, 2002; Georghiou et al., 2003; Weiss and Thurbon, 2006). Hence, in light of the scope and scale of the government procurement market, national governments use their purchasing power to promote the development of domestic productive sectors. Government procurement policy has been at the centre of recent debate on policies to support innovation (Aschoff and Sofka, 2009). However, there is a lack of research on the adoption of government procurement policy as an instrument to stimulate innovation in developing countries (Ribeiro, 2009). This chapter sets out to start filling this gap by attempting to elucidate the role that can be played by government procurement policy in fostering innovation by firms located in developing countries. innovation by firms located in developing countries. The chapter focuses on a specific policy instrument, which is public procurement for innovation (PPI) (Edquist and Zabala-Iturriagagoitia, 2012). In contrast to off-the-shelf purchasing of standardized goods and services, PPI is characterized by the acquisition of goods and services that constitute innovations, but did not exist at the time the procurement call was launched.